Fearful Symmetry : a Study of William Blake. - Frye, Northrop (Princeton University Press, 2013)
This brilliant outline of Blake's thought and commentary on his poetry comes on the crest of the current interest in Blake, and carries us further towards an understanding of his work than any previous study. Here is a dear and complete solution to the riddles of the longer poems, the so-called ""Prophecies, "" and a demonstration of Blake's insight that will amaze the modern reader. The first section of the book shows how Blake arrived at a theory of knowledge that was also, for him, a theory of religion, of human life and of art, and how this rigorously defined system of ideas found expres.